Determination of Heavy Metals in Some Types of Imported Fish from Local Markets - H. Al-Dahhan, Wedad; M. Ahmad, Shayma; Mansour, Omran; Jebali, Jamel; A. Yousif, Emad (Al-Nahrain Journal of Science, 2022)
Heavy metals can be considered in the aquatic environment as natural archaeological components and their quantities have risen as a result of industrial pollution. Heavy metals do not degrade over time and their concentrations can only rise due to bioaccumulation unlike organic contaminants. In the recent period, fish consumption has increased significantly because of its nutritional benefits, as it is a vital source of protein, as well as being high in critical vitamins and minerals. Because of the presence of heavy metals in frozen fish, it is a global public health issue concern but their presence remains essential and important for human physiological activities. However, when concentrations exceed the established allowed limits, they can be detrimental. The aim of this study was to quantify the concentration of heavy metals in frozen fish samples selected from Baghdad’s local markets. Six samples (Cleaned Shrimps, Anchovy Fillets, Captain Fisher Shrimps, Mackerel Fillets, Super Fresh Kalamar Squid and Frozen Rainbow Trout) of common brands of imported fish were selected from Iraqi markets in Baghdad. Acid digestion with a mixture of (65% HNO3 with 37% HCL) was carried out to free heavy metals from fish samples to prepare solutions for testing in atomic absorption spectroscopy (AAS) device. The results reveal that the element concentrations in the selected samples (Cr, Co, Fe, Cu, Ni, K, Zn and Mg) are within the acceptable levels, and are lower than the permitted exposure limits according to international standards. It is remarkable to mention that the quantities of (Cd and Pb) are lower than permissible exposure limits of cadmium (0.2 mg/Kg) and lead (0.5 mg/Kg), implying that these imported items could be consumed safely.